JURIDICAL ANALYSIS OF THE EFFECTIVENESS OF DIGITAL TRANSFORMATION IN RESIDENCE PERMIT SERVICES TO ACHIEVE TRANSPARENCY AND ACCOUNTABILITY (RESEARCH STUDY AT THE CLASS I SPECIAL IMMIGRATION OFFICE TPI BATAM) - Safitry Dianata; Siti Nurkhotijah; Sayid Fadhil (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Digital transformation in public services is a form of adaptation to the development of information technology aimed at improving efficiency, transparency, and accountability. In the immigration sector, residence permit services for foreigners are among the strategic services that demand legal certainty, speed, and accuracy. However, various obstacles are still encountered in its implementation, such as system incompatibility, technical disruptions, low digital literacy, and potential procedural deviations. This study aims to analyse, from a legal perspective, the effectiveness of digital transformation in residence permit services to achieve transparency and accountability at the Class I Special Immigration Office TPI Batam. The methods used in this research are normative and empirical legal research methods. The normative approach reviews relevant laws and regulations, such as the 1945 Constitution of the Republic of Indonesia, Law Number 6 of 2011 concerning Immigration, and Presidential Regulation Number 95 of 2018 concerning the Electronic-Based Government System. Meanwhile, using a socio-legal approach, the empirical approach is carried out through interviews and observations of implementing digital services in the field. The research results indicate that, normatively, the regulations governing the digital transformation of residence permit services are already adequate. However, their effectiveness is still not optimal in practice due to various technical, institutional, and social obstacles. The digital system has driven improvements but does not yet fully ensure transparency and accountability due to weak internal supervision and a lack of human resource support. Therefore, updates to the technological system, human resource training, increased public digital literacy, and tightening regulations and supervision are needed as strategic efforts.